A taxonomic revision of the Neotropical termite genus Cyrilliotermes Fontes (Isoptera, Termitidae, Syntermitinae) - Constantino, Reginaldo; Carvalho, Sérgio H.c. (Zootaxa, 2012)
The taxonomy of the South American termite genus Cyrilliotermes Fontes, 1985 is revised, including an identification keyto soldiers and distribution maps for all species. Two new species are described: C. brevidens and C. crassinasus, bothfrom southeastern Brazil. C. cashassa Fontes, 1985 and C. jaci Fontes, 1985 are both designated as junior synonyms ofC. angulariceps (Mathews, 1977), and C. cupim Fontes, 1985 is designated as a junior synonym of C. strictinasus (Mathews, 1977). An updated diagnosis for the genus is presented, including gut morphology. All species are illustrated.